(untitled) (BIRDEM Medical Journal, 2018)
Background: Clinical phenotype in Klinefelter syndrome (KS) shows utmost contrariety according to the genetic presentation. The karyotype 47, XXY is one of the commonest types of sex chromosomal abnormality in males presenting with infertility, hypogonadism, small penis, gynaecomastia and tall stature. Cytogenetic study is the only way to differentiate between chromosomal abnormality and other androgen deficiency disorders. The aim of this study was to investigate cytogenetic and phenotypic profile of Klinefelter syndrome in a group of referred patients with suspected genetic disorders. Methods: This observational study was carried out at the Cytogenetic Laboratory of the Department of Immunology BIRDEM General Hospital for a period of seventeen years from 2000 to 2016. A total of 9,216 patients suspected for different chromosomal abnormalities (e.g. numerical chromosomal disorders, primary amenorrhoea, ambiguous genitalia etc.) were included in this study referred by physicians of various discipline from different areas of Bangladesh. From the patients referred for cytogenetic study, detailed family history and physical findings were noted. Complete genetic examination and pedigree construction was done to exclude non-chromosomal causes of anomalies. For cytogenetic analysis, peripheral lymphocyte culture by the standard method using the G-banding technique was employed. Results: In this study 1.67% (154) of referred patients were diagnosed as Klinefelter syndrome in cytogenetic study and most of them were diagnosed in their adulthood between 20-29 years of age. Classical cytogenetic form of KS-47, XXY (87%) were most common followed by other mosaic and supernumerary X chromosome aneuploidy. Most of the patients presented with tall stature (61.7%) followed by other features such as gynaecomastia (45.5%), eunuchoid skeleton (29.8%), sexual dysfunction (34.41%), small penis (22.7%), and delayed development of secondary sex characteristics (22.7%). Conclusion: Diagnosis of Klinefelter syndrome in early age before puberty is needed to be differentiated from other related disorders and thereby improving the quality of life by providing appropriate and timely treatment. Therefore, we have to focus to improve our overall capacity to diagnose genetic disorders for proper intervention Birdem Med J 2018; 8(2): 126-131